Hard superconducting nitrides - Chen, Xiao-Jia (National Academy of Sciences, 2005)
Detailed study of the equation of state, elasticity, and hardness of selected superconducting transition-metal nitrides reveals interesting correlations among their physical properties. Both the bulk modulus and Vickers hardness are found to decrease with increasing zero-pressure volume in NbN, HfN, and ZrN. The computed elastic constants from first principles satisfy c(11) > c(12) > c(44) for NbN, but c(11) > c(44) > c(12) for HfN and ZrN, which are in good agreement with the neutron scattering data. The cubic δ-NbN superconducting phase possesses a bulk modulus of 348 GPa, comparable to that of cubic boron nitride, and a Vickers hardness of 20 GPa, which is close to sapphire. Theoretical calculations for NbN show that all elastic moduli increase monotonically with increasing pressure. These results suggest technological applications of such materials in extreme environments.